Quality of designs and features of small urban green spaces in Petaling Jaya Town, Malaysia - Fatiah, A.A.; Ponrahono, Zakiah; Zakariya, Khalilah (Malaysian Institute of Planners, 2021)
Small Urban Green Spaces (SUGS) mushroomed in dense cities as a scaled down version of larger parks. In the past, SUGS are often abandoned, or their quality is often overlooked. The purpose of this study is to explore the design and features to make a good quality SUGS. Five experts were approached with a weightage evaluation to rate its quality based on selected criteria's; Accessibility, Attractiveness, Functionality, and Safety. Each criterion had a variable to measure the construct. Findings from the expert evaluation showed that SUGS were rated medium or low overall quality. The variables that obtained the highest score and attained high-quality ratings were Obstacles (Safety criteria), General Maintenance (Attractiveness criteria), and Play Area (Accessibility criteria). Interview with park users revealed that they preferred the "presence of trees," "well-maintained environment," and "walking path accessibility." The least preferred attributes were "poor maintenance," "dangerous walking path," and "negative perception of safety." Overall, to ensure the quality of SUGS attention should be placed on the Accessibility of its features (e.g., walking path and play area), the attractiveness of the park (e.g., vegetation and maintenance), the functionality of the features (e.g., sports facilities) and perception of Safety (e.g., absence of obstacles).